Research Progress on the Mechanism of Pulsed Light Sterilization and Its Application in Food Field - YE Zihan, WANG Wenjun, ZHOU Jianwei, LÜ Ruiling, LIU Donghong (Shipin Kexue, 2025)
As a new non-thermal food sterilization technology, pulsed light has gradually become a research focus for its advantages of high efficiency, convenience and environmental friendliness. Pulsed light has a strong penetration ability and a wide sterilization spectrum, which has found wide application. Pulsed light can maintain food texture, flavor and taste, making it highly promising for research. However, there is currently a lack of systematic research on the mechanism of pulsed light sterilization; although a wide range of methods have been applied, the synergistic mechanisms between different effects are still not clear. In this context, this paper reviews the mechanism of pulsed light sterilization and its application in the field of foods. First, using VOS viewer software and bibliometric, the current status of research on pulsed light sterilization is analyzed to provide accurate information and clues for understanding the research trends and development directions in the field of pulsed light sterilization technology. Secondly, from the perspectives of its biophysical, photothermal and photochemical effects the process of multi-target, multi-core and multi-system action of pulsed light on bacteria is elucidated to enhance our understanding of the mechanism of pulsed light sterilization. Finally, the application of pulsed light sterilization to different food categories is summarized. In the future, further understanding of the mechanism of pulsed light sterilization and its combination with other sterilization technologies will expand the application scope of food sterilization.